GAMBARAN PENGETAHUAN KADER POSYANDU TENTANG DETEKSI DINI STUNTING DI KELURAHAN XY WILAYAH KERJA PUSKESMAS X PEKANBARU - Soraya Medina Ruza; Ari Diansyah; Siska Silviana; Devi Gusmaiyanto (LPPM Universitas Abdurrab, 2024)
Stunting is one of the most serious issues affecting toddler development in Indonesia. Stunting is the result of persistent starvation in the first 1,000 days of life. Early diagnosis of stunting can be achieved by utilising Posyandu activities that are managed and organised by, for, and with the community, making it easier for the community to access basic health services and accelerating the reduction in maternal and infant death rates. The purpose of this research is to examine the level of knowledge of cadres on early detection of stunting at Community Health Centre. The research method used was a pre-experiment in which cadres were given a pre-test questionnaire to determine their level of knowledge about early detection of stunting, education on early detection of stunting material was provided via lecture, and a post-test was administered following the counselling. This study found that health promotion had a substantial impact on early diagnosis of stunting among posyandu cadres in XY subdistrict using the lecture technique (p-value < 0.05).